2016
DOI: 10.1039/c6ra15948f
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamide-1,3,5-triazine–thiazoles: discovery of a novel class of antidiabetic agents via inhibition of DPP-4

Abstract: Dipeptidyl peptidase-4 (DPP-4) inhibitors are a novel class of antidiabetic drugs used for treating type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Furthermore, the presence of additional aromaticity did not influence the activity. Moreover, molecular docking results indicated that, ligand 157 was efficiently docked into the active site of the catalytic triad of Ser 630, Asp 708 and His 740 encompassing both S1 and S2 pocket with CDOCKER interaction energy of 57.80 [91]. At last, Iqbal and co-workers have developed arylsulfonylspiroimidazolidine-2,4-dione hybrids as potent hypoglycemic and ALR2 agents.…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…Furthermore, the presence of additional aromaticity did not influence the activity. Moreover, molecular docking results indicated that, ligand 157 was efficiently docked into the active site of the catalytic triad of Ser 630, Asp 708 and His 740 encompassing both S1 and S2 pocket with CDOCKER interaction energy of 57.80 [91]. At last, Iqbal and co-workers have developed arylsulfonylspiroimidazolidine-2,4-dione hybrids as potent hypoglycemic and ALR2 agents.…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…[18][19][20] However, GLP-1 exerts a short in vivo active duration due to the dipeptidyl peptidase IV (DPP-IV) digestion and rapid renal ltration, which severely limit its application in diabetes therapies. [21][22][23] According to our previous research, 24 the strategy to obtain the extended half-lives of peptide drugs was performed by fusing the peptide drugs with a lipidated the heptapeptide tags exerting high affinity for HSA. In order to develop the GLP-1 receptor agonist with prolonged active duration, we reoptimized the previous tags and fused the tag to the mutated GLP-1(7-37) via a thrombin-cleavable linker to construct novel GLP-1R agonist pro-drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, derivatives of 1,3,5‐triazine have received considerable attention . 1,3,5‐Triazines have various pharmacological activities, such as antibacterial, antifungal, antimalarial, antidiabetic and anticystic fibrosis effects. Moreover, 1,3,5‐triazine exerts anticancer effects by inhibiting PI3K/mTOR, Rad6 ubiquitin conjugating enzyme and human epidermal growth factor receptor tyrosine kinases (EGFR‐TKs) …”
Section: Introductionmentioning
confidence: 99%